Memory, Trauma, and Identity - Eyerman, Ron (Cultural Sociology, 2019)
This volume brings together Ron Eyerman's most important interventions in the field of cultural trauma and offers an accessible entry point into the origins and development of this theory and a framework of an analysis that has now achieved the status of a research paradigm. This collection of disparate essays, published between 2004 and 2018, coheres around an original introduction that not only provides a historical overview of cultural trauma, but is also an important theoretical contribution to cultural trauma and collective identity in its own right. The Afterword from esteemed sociologist Eric Woods connects the essays and explores their significance for the broader fields of sociology, behavioral science, and trauma studies.